Development of Teaching Materials For Receptive Language Skills In The Area of Listening Comprehension Using Thunkable - Rosmaini Rosmaini; Ika Febriana; Diah Eka Sari (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
In the era of technology-based learning, the need for interactive and adaptive digital instructional materials is becoming increasingly urgent, particularly for receptive language skills such as listening, which have traditionally received less attention than productive skills. However, the instructional materials available in the Indonesian Language and Literature Education Program at Medan State University remain limited and have not yet optimally utilized technology to support listening comprehension. This study develops listening skills instructional materials based on the Thunkable app as a form of digital learning innovation, while also representing a novelty in integrating a mobile app development platform into listening comprehension instruction—an area that has not been extensively explored to date. The study employed a seven-step research and development (R&D) methodology, involving students from the Indonesian Language and Literature Education Program as test subjects, as well as validation by subject matter experts, linguists, and media experts, supplemented by evaluations from learning practitioners (teachers and lecturers). The results of the study show that the developed teaching materials received an average validation and evaluation score of 87.43%, which falls into the “very good” category. These findings confirm that Thunkable-based instructional materials are not only suitable for use in college courses but also help enrich the variety of digital learning resources and enhance students’ engagement and comprehension in listening skills.